BCG vaccination induces enhanced frequencies of dendritic cells and altered plasma levels of type I and type III interferons in elderly individuals. (September 2021) - Kumar, Nathella Pavan; Padmapriyadarsini, Chandrasekaran; Rajamanickam, Anuradha; Bhavani, Perumal Kannabiran; Nancy, Arul; Jeyadeepa, Bharathi; Selvaraj, Nandhini; Ashokan, Dinesh; Renji, Rachel Mariam; Venkataramani, Vijayalakshmi; Tripathy, Srikanth; Babu, Subash
Highlights: BCG vaccination induces significantly enhanced frequencies of DC subsets BCG vaccination induces diminished plasma levels of type I interferons but increased levels of type III interferons BCG vaccination can potentially boost immune responses in a non -specific or off-target manner in elderly individuals. Abstract: Objective: BCG can improve the response to vaccines directed against viral infections, and also, BCG vaccination reduces all-cause mortality, most likely by protecting against unrelated infections. However, the effect of BCG vaccination on dendritic cell (DC) subsets is not well characterized. Methods: We investigated the impact of BCG vaccination on the frequencies of DC subsets and type I and III interferons (IFNs) using whole blood and plasma samples in a group of elderly individuals (age 60-80 years) at one-month post-vaccination as part of our clinical study to examine the effect of BCG on COVID-19. Results: Our results demonstrate that BCG vaccination induced enhanced frequencies of plasmacytoid DC (pDC) and myeloid DC (mDC). BCG vaccination also induced diminished plasma levels of type I IFNs, IFNα and IFNβ but increased levels of type III IFNs, IL-28A and IL-29. Conclusions: Thus, BCG vaccination was associated with enhanced DC subsets and IL-28A/IL-29 in elderly individuals, suggesting its ability to induce non-specific innate immune responses.